Distribusi Komponen Darah Thrombocyte Concentrate (TC) - Gina Almirah; Nurpuji Mumpuni; Fransisca Romana Sri Supadmi (Jaringan Laboratorium Medis, 2020)
Blood transfusions become an important component in the management of patients with injuries to cases of accidents, surgical conditions, violence, pregnancy complications, anemia, hemodialysis, and other medical conditions. The blood transferred can be complete blood and blood components such as Packed Red Cells (PRC), Thrombocyte Concentrate (TC), Anti hemophilia Factor (AHF)/Cryoprecipitate, Fresh Frozen Plasma (FFP), Buffy Coat (BC), Liquid Plasma (LP). This research aims to determine the distribution of blood component Thrombocyte Concentrate (TC) in Indonesian Red Cross Blood Transfusion Service Pontianak City. The design of this research is a quantitative study with a descriptive design, the approach of time used is retrospective by collecting and processing all the distribution data of blood component Thrombocyte Concentrate (TC) in Indonesian Red Cross Blood Transfusion Service Pontianak City in 2019. Processing and analyzing data in this study using the Statistical Product and Service Solutions (SPSS) application. Data analysis results of the number of Thrombocyte Concentrate requests 5,427 bags in 12 months, with an average (Mean) of 452.25 and a data spread (Std. Deviation) of 224.620 is greater than the dosage amount and the distribution of Thrombocyte Concentrate 3,444 bags in 12 months, with an average (Mean) 287 and a data spread (Std. Deviation) 79.681. The most demand and distribution is Dr. Soedarso country general hospital, while the fewest are the Nabasa maternity hospital. The distribution of Thrombocyte Concentrate blood components in Indonesian Red Cross Blood Transfusion Service Pontianak City still needs improvement for both inventory and distribution to be fulfilled the number of Thrombocyte Concentrate requests.